High‐performance adsorptive desulfurization by ternary hybrid boron carbon nitride aerogel. Issue 9 (15th May 2021) - Luo, Jing; Wang, Chao; Liu, Jixing; Wei, Yanchen; Chao, Yanhong; Zou, Yiru; Mu, Liping; Huang, Yan; Li, Huaming; Zhu, Wenshuai
Abstract: Separation of aromatic organosulfur compounds is vital for upgrading the feed to clean fuel products, however, it remains a formidable challenge for the present adsorbents. Herein, a series of novel aerogel‐like boron carbon nitride (BCN) with three‐dimensional interconnected porous networks were fabricated via a hydrogel template and freeze‐casting strategy. The as‐prepared aerogel‐like BCN had a variable carbon content and a flexible size of graphene domain on its porous structure. The optimal BCN aerogel represents the top‐level of adsorptive desulfurization (ADS) capacity for aromatic organosulfur compounds (30.8 mg S/g adsorbent), strikingly higher than the state‐of‐the‐art aerogels adsorbents (17.1 mg S/g adsorbent) reported under similar conditions. A selective adsorption for dibenzothiophene in the presence of aromatic hydrocarbons, nitrogen compounds were also achieved on BCN aerogel. The adsorption isotherm and XPS measurement reveal heterogeneous adsorption on the BCN aerogel via π–π and Lewis acid–base interactions.